Rasionalitas Ekonomi : Homo Ekonomicus VS Homo Islamicus (Analisis Terhadap Sistim Ekonomi) - Siregar, Rosnani (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2012)
Sharia  economy  has  an  economic  system characteristics  that  it  is  own  economic  system,  can  be  said  to have differences with other economic systems. All facilities and infrastructure that is used to obtain the necessities of life in the world is not solely oriented to the life of the world alone but are closely related to the afterlife. While other economies;  capitalist and  socialist  economies  are  solely  oriented  to  the  life  of  the world  alone.  Shariah  economic  rationality  can  be  seen  on  the economic principles of Sharia and the basic principles of system used.  Principle  -  the  principle  of  Islamic  Economics,  are  the justice  and  sociological value of wealth. The basic principle of Islamic  banking  system  is  profit-sharing  system  as  an alternative.  Capitalist economic system which gives freedom to every individual to exploit the earth. The capitalist system has several  indicators;  No  uniform,  no  harmony,  con-profit, materialistic,  moral  crisis,  aside  Welfare.  Socialist  Economic System are  all forms of  production and sources of revenue to the state-owned and regulated by the state then, used to all the people. There is no free will on economic system of society that it is contradiction to the human right it shelf.